2020
DOI: 10.1093/jscr/rjaa041
|View full text |Cite
|
Sign up to set email alerts
|

The use of decompressive segmental sublaminoplasty to treat myelopathy caused by lumbar stenosis in tethered cord syndrome

Abstract: A 79-year-old woman presented with acute-onset right leg pain in the setting of 3 months of progressive gait deterioration and bilateral leg weakness. On exam she had right lower extremity hyperreflexia and weakness. Lumbar spine magnetic resonance imaging demonstrated L3–L5 central canal stenosis with L4–L5 spondylolisthesis and a previously undiagnosed tethered cord. She underwent minimally invasive left segmental sublaminoplasty at L3–L4 and L4–L5 for spinal cord decompression with onlay arthrodesis resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In terms of the appropriate surgical strategy in such cases, recent authors [10][11][12] have demonstrated improvement in symptoms only after decompressive surgery for the treatment of LCS. However, the symptoms in these cases were due to compression myelopathy with LCS instead of TCS.…”
Section: (C) Four Months After the Second Surgery Serial Sagittal Vie...mentioning
confidence: 99%
“…In terms of the appropriate surgical strategy in such cases, recent authors [10][11][12] have demonstrated improvement in symptoms only after decompressive surgery for the treatment of LCS. However, the symptoms in these cases were due to compression myelopathy with LCS instead of TCS.…”
Section: (C) Four Months After the Second Surgery Serial Sagittal Vie...mentioning
confidence: 99%